DAGESTAN RUSSIANS ON THE STATE OF INTERETHNIC SITUATION IN THE REPUBLIC - Sahbanova, M M; Lysenko, U M; Mamaraev, R M (History, Archeology and Ethnography of the Caucasus, 2015)
The authors of the article present the assessment of the interethnic situation in Dagestan existing in the mass consciousness of ethnic Russians living in Dagestan, possible factors of its deterioration, and the reasons for the formation of intolerance in the public conscience of the Russian-speaking population of the republic,positive / negative attitude towards migration of the representatives of their own and other ethnic communities.